Prevalence and associations of dry eye disease and meibomian gland dysfunction in the ural eye and medical study - Bikbov, Mukharram; Gilmanshin, Timur R.; Zainullin, Rinat M.; Kazakbaeva, Gyulli M.; Iakupova, Ellina M.; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Panda-Jonas, Songhomitra; Rusakova, Iuliia A.; Nuriev, Ildar F.; Zaynetdinov, Artur F.; Miniazeva, Liana A.; et al. (Scientific reports, 2022)
To assess the prevalence of dry eye disease (DED) and Meibomian gland dysfunction (MGD) in a population in Russia. The population-based Ural Eye and Medical Study was conducted in an urban and rural region in Bashkortostan/Russia and included 5899 (80.5%) out of 7328 eligible persons, aged 40 + years. DED and MGD were assessed by Schirmer´s test, slit-lamp based examination of the Meibomian glands, and an interview with DED-related questions. The study included 5153 (87.4%) individuals with DED and MGD assessments (mean age: 58.5 ± 10.5 years). The mean Schirmer´s test result was 11.8 ± 6.8 mm and 12.5 ± 7.1 mm for the right/left eye, with a result of ≤ 5 mm measured in 1098 (21.3%; 95% confidence intervals (CI) 20.2, 22.4) of the worse eyes. The mean subjective dry eye symptoms score was 1.37 ± 1.82. MGD grade 1 (telangiectasia at the lid margin), 2, 3, 4 or any grade in the worse eye was diagnosed in 901 (21.1%), 1161 (27.1%), 158 (3.7%), 32 (0.7%), and 2252 (52.6%; 95% CI 51.1, 54.1) eyes respectively. The prevalence of DED diagnosis #1, #2 and #3 (Schirmer´s test ≤ 5 mm, and dry eye score ≥ 1, ≥ 2, and ≥ 3, respectively), #4 (dry eye score ≥ 1, Schirmer test ≤ 5 mm, MGD grade 1 +), and #5 (dry eye score ≥ 1, Schirmer test ≤ 5 mm, MGD grade 2 +) were 598/5142 (11.6%), 426/5153 (8.3%), 273/5142 (5.3%), 335/5142 (6.5%), and 186/5142 (3.6%), respectively. Mean depression score as applied was 5.1 ± 3.8. Higher DED prevalence (definition #4) was associated (multivariable analysis) with female sex (odds ratio (OR) 1.71; 95% CI 1.31, 2.22; P < 0.001), higher depression score (OR 1.04; 95% CI 101, 1.07; P = 0.009), and higher prevalence of thyroid disease history (OR 1.63; 95% CI 1.19, 2.24; P = 0.006). DED and MGD were common in this rural and urban population, and their prevalence was associated with female sex, thyroid disease, and depression.
Gesehen am 04.07.2023